Perovskite solar cells: Li–TFSI and t-BP-based chemical dopant engineering in spiro-OMeTAD. Issue 6 (19th January 2023) - Lin, Fangyan; Luo, Junsheng; Zhang, Yunpeng; Zhu, Jinqing; Malik, Haseeb Ashraf; Wan, Zhongquan; Jia, Chunyang
Abstract : The advances in the modification of the bi-dopant Li–TFSI/ t -BP system in doping spiro-OMeTAD for high efficiency and stable perovskite solar cells are summarized. Abstract : Organic–inorganic lead halide perovskite solar cells (PSCs) offer promising aspects such as high efficiency, low-cost, and flexible. The booming growth of PSCs cannot be achieved without the application of chemical dopant engineering. The hole-transporting layer (HTL) in PSCs are critical for predicting device performance and are a major bottleneck for further improving device stability and efficiency. Li–TFSI/ t -BP, which are widely used in the doping of hole-transporting materials (HTMs), are essential for the preparation of high-performance devices, and although many novel dopants have been reported, the state-of-the-art devices are still based on this bi-doping system. This review summarizes the latest advances in the modification of the Li–TFSI/ t -BP bi-doping system in PSCs. It systematically presents the mechanism of Li–TFSI/ t -BP doping of spiro-OMeTAD and the major factors affecting this doping reaction. The modification strategy of the Li–TFSI/ t -BP bi-doping system and the application of co-dopant in this system have been focused on. In addition, the selection of doping methods for different doping systems, mainly divided into liquid–liquid, liquid–solid, and gas–solid contact doping methods, is briefly introduced. Finally, the corresponding design principles of the doping system and the subsequent development perspectives in this field are discussed in detail.